2000
DOI: 10.1038/labinvest.3780158
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Denervation of Human Detrusor after Spinal Cord Injury

Abstract: SUMMARY:The bladder receives an extensive nerve supply that is predominantly cholinergic, but several putative transmitters are present, some of which are colocalized. Previous studies have shown increased levels of sensory nerves, reduced inhibitory transmitters, and structural and functional changes in the excitatory input in unstable bladder conditions. The present study compared the end-organ nerve supply to the bladder in spinal cord injury (SCI) with uninjured controls. Acetylcholinesterase histochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 34 publications
10
37
0
2
Order By: Relevance
“…Supporting this, Smet et al (1997) found that the density of CGRP and SP-immunoreactive nerves within the subepithelium was increased by 82% in women with urodynamically proven detrusor overactivity compared with control without any lower urinary tract symptoms. In patients with spinal cord injury, the subepithelial nerve plexus and its density of CGRPcontaining nerves were reduced (Drake et al, 2000).…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…Supporting this, Smet et al (1997) found that the density of CGRP and SP-immunoreactive nerves within the subepithelium was increased by 82% in women with urodynamically proven detrusor overactivity compared with control without any lower urinary tract symptoms. In patients with spinal cord injury, the subepithelial nerve plexus and its density of CGRPcontaining nerves were reduced (Drake et al, 2000).…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…A few groups have already demonstrated striking structural characteristics and functional potential of bladder ICs. [1][2][3] Nerve ganglia in the bladder wall and in the pelvic plexus contain multitudinous connections, and express a diverse range of putative transmitters; [4][5][6] current understanding of their functional properties is limited.…”
Section: Cellular Phenotypes Present In the Bladdermentioning
confidence: 99%
“…75 Galanin is widely distributed in enteric nerve terminals and acts to modulate intestinal motility by altering smooth muscle contraction and in the human colon, alterations in Gal1-R expression may have an important role in colitis. 76 Indeed, inflammation up-regulates this receptor by an NF-B-dependent pathway.…”
Section: Galanin R1mentioning
confidence: 99%